Character Education in the 21st Century: The Relevance of Abdul Wahhab Ash Syarani’s and Thomas Lickona’s Concepts - Muhamad Arif; Yuldashev Azim Abdurakhmonovich; Sulaiman Dorloh (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IPMAFA, 2023)
This article addresses the development of education and technology in the 21st century society. In order for education to function efficiently, the need of moral/character education is a necessary step in preserving its survival. In this study, the researcher was interested in Ash Syarani's theory of moral education because of its relation to the findings of Thomas Lickona's theory (moral knowing, moral feeling, and moral action) in education in the twenty-first century. This study utilized a literature review approach. Ash Syarani's Minahus Saniyah and Lickona's Teaching for Character: How Schools Can Teach Respect and Responsibility are the key data sources. While content analysis from Elo and Marsh was employed for data analysis in this study, The notion presented in Shaykh Abdul Wahhab Ash Syarani's book Minahus Saniyah is more applicable to Indonesian culture, particularly in studies that provide more real-world examples and are not confined to concepts (such as character education from Thomas Lickona's theory). The repercussions are fairly real that this analysis addresses the concept of moral education that is still relevant (in Thomas Lickona's theory; moral knowing, moral feeling, and moral action) for implementation in Indonesian education in the twenty-first century.